2023
DOI: 10.14202/vetworld.2023.380-385
|View full text |Cite
|
Sign up to set email alerts
|

Potential protective effects of red grape seed extract in a rat model of malathion-induced neurotoxicity

Abstract: Background and Aim: Exposure to pesticide mixtures used in agricultural practice poses a grave risk to non-target animals. This study aimed to determine whether red grape seed extract (RGSE, which is 95% bioflavonoids and equal to 12,000 mg of fresh red grape seed, and 150 mg of vitamin C) alleviated the changes in brain-derived neurotrophic factor (BDNF) level, acetylcholinesterase activity, oxidative stress, and apoptosis induced by orally administered malathion in a rat model of malathion-induced neurotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…It has previously been observed that supplementing with LCP or GSE reduced MDA levels in the heart tissue and, as a result, lipid peroxidation, indicating a lower risk of coronary heart disease [44][45]. Previous research has indicated that LCP is the most effective biological carotenoid singlet oxygen quencher and that it contributes to the initial line of defense that is upheld by SOD and CAT [46].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been observed that supplementing with LCP or GSE reduced MDA levels in the heart tissue and, as a result, lipid peroxidation, indicating a lower risk of coronary heart disease [44][45]. Previous research has indicated that LCP is the most effective biological carotenoid singlet oxygen quencher and that it contributes to the initial line of defense that is upheld by SOD and CAT [46].…”
Section: Discussionmentioning
confidence: 99%